Edge-illumination X-ray dark-field imaging for visualising defects in composite structures. (15th December 2015) - Endrizzi, M.; Murat, B.I.S.; Fromme, P.; Olivo, A.
Abstract: Low velocity impact can lead to barely visible and difficult to detect damage such as fibre and matrix breakage or delaminations in composite structures. Drop-weight impact damage in a cross-ply carbon fibre laminate plate was characterised using ultrasonic C-scan measurements. This was compared to the results provided by a novel X-ray imaging technique based on the detection of phase effects, which can be implemented with conventional equipment. Three representations of the sample are provided: absorption, differential phase and dark-field. The latter is of particular interest to detect cracks and voids of dimensions that are smaller than the spatial resolution of the imaging system. The ultrasonic C-scan showed a large delamination and additional damage along the fibre directions. The damage along the fibre directions and other small scale defects were detected from the X-ray imaging. As the system is sensitive to phase effects along one direction at a time, the acquisition of an additional scan, rotating the sample 90° around the beam axis, provides information in both fibre directions. These two techniques enable access to a set of complementary information, across different length scales, which can be useful in the characterisation of the defects occurring in composite structures.